Activity Of Women From Khorezm At The Front During The Second World War (Eurasian Journal of History, Geography and Economics, 2022)
In this article, information about the women from the Khorezm region, who bravely fought alongside men for the peace and freedom of their homeland in the active army during the Second World War, is disclosed based on the analysis of archive documents.